Genetic testing identifies the potential risk of multiple endocrine neoplasia in a Vietnamese family - Hai Ha, Nguyen; Thi Thanh Hoa, Nguyen; Thi Dung, Pham; Huy Binh, Nguyen; Dang Ton, Nguyen (Vietnam Journal of Biotechnology, 2020)
Multiple endocrine neoplasia type 2A (MEN2A) is a rare syndrome characterized by the presence of medullary thyroid carcinoma, pheochromocytoma, hyperparathyroidism and sometimes cutaneous lichen amyloidosis. This syndrome is caused by a germline activation mutation in the rearranged during transfection (RET) proto-oncogene transmitted by an autosomal dominant inheritance. In this study, we reported a rare case of a 44-year-old man from Vietnam with medullary thyroid carcinoma and pheochromocytoma as the symptom of MEN2A. Genetic testing indicated a nucleotide substitution located in exon 11 of the RET proto-oncogene (c.1900T>C, p.C634R), which was reported as a known pathogenic mutation of MEN2A. Further genetic tests on the other family members found the same mutation in his daughter (currently 14 years-old) and his son (currently 8 years-old). Although these 2 children do not yet have any manifestations of MEN2A, this data emphasizes their high risks of this disease. Therefore, this case draws attention to the importance of genetic counselling in C634R carriers, as well as rigorous follow-up appointments to reduce incidence and mortality since the mutation is classified as a high-risk group within the medullary thyroid carcinoma guidelines.